Application of chatbots based on NLP technology for more effective learning of foreign languages, using English as an example; Язык. Общество. Образование - Цуркан К. А. (2024, 2024)
The paper describes the working principle of chatbots based on Natural Language Processing (NLP) technology. It describes the mechanisms of chatbots’ understanding of user requests, evaluation of user’s foreign language proficiency level, as well as the mechanism of introducing chatbots into the curriculum for group and individual student's work